2010
DOI: 10.3109/0142159x.2010.509420
|View full text |Cite
|
Sign up to set email alerts
|

Students’ reflections in a portfolio pilot: Highlighting professional issues

Abstract: Background: Portfolios are highlighted as potential assessment tools for professional competence. Although students' selfreflections are considered to be central in the portfolio, the content of reflections in practice-based portfolios is seldom analysed. Aim: To investigate whether students' reflections include sufficient dimensions of professional competence, notwithstanding a standardized portfolio format, and to evaluate students' satisfaction with the portfolio. Methods: Thirty-five voluntary final-year m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Results revealed that the students liked portfolios that presented their strengths and weaknesses in a structured manner, and they were satisfied that the system contained a mechanism for instructor feedback to improve their reasoning skills. 13 Current challenges lie in how to continue recording student grades and provide evidence of their abilities to assess and evaluate learning outcomes. 9,12 E-portfolios must be designed with an understanding of user attitudes and preferences to enable successful technology use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that the students liked portfolios that presented their strengths and weaknesses in a structured manner, and they were satisfied that the system contained a mechanism for instructor feedback to improve their reasoning skills. 13 Current challenges lie in how to continue recording student grades and provide evidence of their abilities to assess and evaluate learning outcomes. 9,12 E-portfolios must be designed with an understanding of user attitudes and preferences to enable successful technology use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12 Professional abilities involve not only knowledge accumulation, but also the nurturing of attitude and values, communication, and clinical reasoning skills. 13 Although these learning processes are not easily assessed using traditional pen-and-paper methods, e-portfolios can record these learning experiences. In one study, mixed-methods research was used to investigate final-year medical students' satisfaction with e-portfolio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study of 114 dietetic students from 11 English universities, viewed portfolios as a satisfactory method of assessment (Brennan and Lennie, 2010). In a qualitative analysis of portfolios submitted by 35 post graduate doctors in Sweden, it was suggested that this method of assessment provided an opportunity for reflection on professional and ethical issues (Haffling et al, 2010). In the context of non-medical prescribing, studies have reported that students have felt prepared for practice on qualification (Boreham et al, 2013) and have discussed approaches to prescribing assessment (Nuttall, 2013;McEwan and Taylor, 2007) but none of these reported the effectiveness of assessment in the context of safe prescribing practice.…”
Section: Introductionmentioning
confidence: 99%
“…Reflection can build 'mindfulness' about feedback received (Bangert-Drowns et al 1991), and can also provide a mechanism for analysing learning deficits (Marton, Hounsell, and Entwistle 1984). Models of reflective practice (Schön 1987) apply across many professional contexts (Connaughton and Edgar 2011), including the health professions such as nursing, psychology, physiotherapy and medicine (Haffling et al 2010). Schön's conceptualisation of reflection as falling into three stages, namely conscious reflection, criticism and action, has influenced the incorporation of reflective journal entries (Boud 2001;Boyd 2002;O'Connor and Hyde 2005) or group discussion processes (Platzner, Blake, and Ashford 2000) into university curricula.…”
Section: Introductionmentioning
confidence: 99%